BRCA1 mislocalization leads to aberrant DNA damage response in heterozygous ABRAXAS1 mutation carrier cells. (20th October 2019) - Bose, Muthiah; Sachsenweger, Juliane; Laurila, Niina; Parplys, Ann Christin; Willmann, Jonas; Jungwirth, Johannes; Groth, Marco; Rapakko, Katrin; Nieminen, Pentti; Friedl, Thomas W P; Heiserich, Lisa; Meyer, Felix; et al.
Abstract: Whilst heterozygous germline mutations in the ABRAXAS1 gene have been associated with a hereditary predisposition to breast cancer, their effect on promoting tumourigenesis at the cellular level has not been explored. Here, we demonstrate in patient-derived cells that the Finnish ABRAXAS1 founder mutation (c.1082G > A, Arg361Gln), even in the heterozygous state leads to decreased BRCA1 protein levels as well as reduced nuclear localization and foci formation of BRCA1 and CtIP. This causes disturbances in basal BRCA1-A complex localization, which is reflected by a restraint in error-prone DNA double-strand break repair pathway usage, attenuated DNA damage response and deregulated G2-M checkpoint control. The current study clearly demonstrates how the Finnish ABRAXAS1 founder mutation acts in a dominant-negative manner on BRCA1 to promote genome destabilization in heterozygous carrier cells. Graphical Abstract: